DESIGNING WRISTBANDS AS A WALKING AID FOR THE ARDUINO NANO-BASED VISUALLY IMPAIRED - Budi Prijo Sembodo; Moh. Thoyib (BEST, 2020)
In the 4.0 era, walking aids for the visually impaired are needed, especially when the user is indoors and outdoors. There are already many tools created, one of which the author wants to make is a wristband. Components include: Ultrasonic Sensor HC-SR04, Arduino Nano, Servo SG90 Motor, and Buzzer. The stages in this study are designing hardware, designing programs, and implementing and testing tools. The testing carried out on this tool is to read the results of objects with distances of 80cm, 90cm, 100cm, 110cm and 120cm. Not only did it test the distance, it also tested the rotation angle performed by the servo motor to drive ultrasonic sensors by 0o,60o,and 120o. It aims to be able to detect in any direction. The results of this tool test have a repeatability rate of 98%, as well as a 97.33% success rate for detecting objects.